PENENTUAN KELAYAKAN PENERIMA KREDIT PADA PT. BANK SULTRA MENGGUNAKAN METODE FORWARD CHAINING DAN TECHNIQUE FOR ORDER PREFERENCE BY SIMILARITY TO IDEAL SOLUTION - Made Aldiantara; Henny Henny; Ilin Sukma (Simtek : jurnal sistem informasi dan teknik komputer, 2026)
To avoid the risk of delayed or non-performing loans, a company must analyze and verify the data of prospective debtors to ensure that it selects truly responsible individuals. Therefore, the author will develop a decision support system to assist in determining the eligibility of loan recipients. The methods used are the Forward Chaining method and the TOPSIS (Technique for Order Preference by similarity to Ideal Solution) method. In building this system, several user interface designs are involved, including: the login page interface design, the registration page interface design, the dashboard page interface design, the customer data page interface design, the add customer data page interface design, the criteria page interface design, the add criteria page interface design, the sub-criteria page interface design, the add sub-criteria data page interface design, the forward chaining rules page interface design, the add forward chaining rules page interface design, and the ranking page interface design. The results of this study are expected to help simplify the process of analyzing the profiles and documents of prospective debtors to determine their loan eligibility, and assist in decision-making for the selection of new loan applicants.